2022
DOI: 10.3389/frwa.2021.750673
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With E. coli Levels in and Salmonella Contamination of Agricultural Water Differed Between North and South Florida Waterways

Abstract: The microbial quality of agricultural water is often assessed using fecal indicator bacteria (FIB) and physicochemical parameters. The presence, direction, and strength of associations between microbial and physicochemical parameters, and the presence of human pathogens in surface water vary across space (e.g., region) and time. This study was undertaken to understand these associations in two produce-growing regions in Florida, USA, and to examine the pathogen ecology in waterways used for produce production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…While other studies have examined the association between geospatial, physiochemical, and meteorological factors and foodborne-pathogen prevalence in the produce preharvest environment (12,14,15,17,20,21,(23)(24)(25)(26)(27)(28)(29), to our knowledge, no research has used advanced statistical methods to model weather, land use, and subregional data on pathogen prevalence in Virginia, specifically the Eastern Shore of Virginia. The Eastern Shore of Virginia has been associated with several salmonellosis outbreaks linked to tomatoes from 2002 to 2010 (1,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While other studies have examined the association between geospatial, physiochemical, and meteorological factors and foodborne-pathogen prevalence in the produce preharvest environment (12,14,15,17,20,21,(23)(24)(25)(26)(27)(28)(29), to our knowledge, no research has used advanced statistical methods to model weather, land use, and subregional data on pathogen prevalence in Virginia, specifically the Eastern Shore of Virginia. The Eastern Shore of Virginia has been associated with several salmonellosis outbreaks linked to tomatoes from 2002 to 2010 (1,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other produce-growing regions have compared microbial quality between both inter-and intrastate growing regions and have also observed some regional differences (12,13,15,17,26). For instance, Salmonella levels (most probable number [MPN]/100 mL) in water had an average MPN of CFU/100 mL approximately 2 log higher when water temperature was .26.7°C, regardless of region in Florida (United States), but at lower water temperatures (#26.7°C), Salmonella levels in water were 1 log CFU MPN/100 mL higher in South Florida than North Florida (12). The findings reported here, and in previous studies, highlight differences in Salmonella prevalence between intrastate growing regions and suggest the importance of performing risk assessments and management at local and regional scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings highlight a key knowledge gap in pre‐harvest studies, as soil, soil amendments, and irrigation water have all been highlighted as key vectors of pathogen contamination of produce (Alegbeleye et al., 2018). Specifically, several previous reports have shown that the survival of pathogens in soil and soil amendments can be influenced by factors such as moisture content and temperature (Sharma et al., 2016; Underthun et al., 2017), and the survival of pathogens in irrigation water can be influenced by factors such as pH, temperature, and turbidity (Murphy et al., 2022; Sharma et al., 2020; Weller et al., 2020). Therefore, more intensive reporting of these key characteristics can provide better insight into population dynamics outcomes on produce in pre‐harvest studies.…”
Section: Resultsmentioning
confidence: 99%